A Novel Series of Pyrazole and Thiadiazole Derivatives Bearing Nabumetone Moiety: Design, Molecular Docking Study, Synthesis, Characterization, and Preliminary Pharmacological Evaluation - Safa A. Mahmood; Monther F. Mahdi; Ayad M R Rauf (Iraqi Journal of Pharmaceutical Sciences, 2025)
A series of new pyrazole and thiadiazole compounds including the Nabumetone moiety were conceptualized, produced, and subjected to assessment for their anti-inflammatory potential against cyclooxygenase enzyme 2. Following an Insilico test involving molecular docking analysis, the most promising compound set was synthesized and further described. After prediction of their activity by molecular docking study using Cambridge Crystallographic Data Base software tool (GOLD), We tested them in real in vivo as anti-inflammatory agents using egg white procedure. Hydrogen bonding interaction with key amino acids in COX-2 isozymes, including Arginine120, Tyrosine355, and Serine530, gave the compounds investigated in molecular docking much higher activity than the reference drugs naproxen, diclofenac, and 6MNA. The data obtained from docking studies were highly correlated with that obtained from the in vivo assay. Compounds 3c, 4c, 5c showed a PLP fitness 91.35, 89.66 and 92.09 respectively, which are the best scores from all synthesized compounds. This research offered helpful direction for the identification of novel pyrazole and thiadiazole anti-inflammatory compounds.